2002
DOI: 10.1046/j.1365-2672.2002.01662.x
|View full text |Cite
|
Sign up to set email alerts
|

Transformation and expression of an anaerobic fungal xylanase in several strains of the rumen bacteriumButyrivibrio fibrisolvens

Abstract: Aims:  To obtain reliable transformation of a range of Butyrivibrio fibrisolvens strains and to express a Neocallimastix patriciarum xylanase gene in the recipients. Methods and Results:  Eight strains (H17c, E14, LP1309, LP1028, AR11a, OB156, LP210B and LP461A) of Bu. fibrisolvens were transformed by the Gram‐positive vector pUB110. A xylanase expression/secretion cassette containing Bu. fibrisolvens promoter and signal peptide elements fused to catalytic domain II of the N. patriciarum x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 47 publications
(48 reference statements)
0
16
0
Order By: Relevance
“…¢brisolvens [195,205]. GH 10 and GH 11 xylanases di¡er in their catalytic properties [206] and it was reasoned that the introduction of a GH 11 xylanase would increase its ability to digest ¢ber [195]. Fiber digestibility could be improved in vitro by more than 28% in comparison with the native untransformed strain [195].…”
Section: Genetically Modi¢ed ¢Ber-degrading Bacteriamentioning
confidence: 99%
“…¢brisolvens [195,205]. GH 10 and GH 11 xylanases di¡er in their catalytic properties [206] and it was reasoned that the introduction of a GH 11 xylanase would increase its ability to digest ¢ber [195]. Fiber digestibility could be improved in vitro by more than 28% in comparison with the native untransformed strain [195].…”
Section: Genetically Modi¢ed ¢Ber-degrading Bacteriamentioning
confidence: 99%
“…1997). Heterologous expression of two fungal ( Neocallimastix patriciarum ) xylanase constructs (xynA and pUMSX in the plasmid vector pUB110) was recently obtained in B. fibrisolvens H17c (Gobius et al. 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The signal peptide in pUMSX encodes a higher proportion of hydrophobic residues to enable more efficient export of the enzyme (Xue et al. 1997; Gobius et al. 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, four strains of recombinant bacteria were trans-inoculated into sheep before fluoroacetate treatment was conducted and it was observed that the inoculated sheep showed reduced toxicity symptoms compared to uninoculated sheep. As B. fibrisolvens is primarily hemicellulolytic (Dehority 1965;Dehority & Scott 1967), a further recombinant of B. fibrisolvens encoding the genes of plant cell wall-degrading enzymes has been constructed to maximize its fibre degradation, and improve digestibility (Cotta et al 1997;Gobius et al 2002;Krause et al 2001b). However, it still failed to outperfom the far more potent fibrolytic rumen bacteria, Fibrobacter and Ruminococcus species (Krause et al 2003).…”
Section: Trans-inoculation Of Rumen Microbementioning
confidence: 99%
“…Therefore, any introduction of genetically modified strains that can digest crystalline cellulose would go a long way in improving the digestive functions of the rumen, allowing for a more diverse diet. Attempts to introduce genetically modified transformation of B. fibrisolvens with fungal xylanase have been considered unsuccessful due to the inability of these strains to compete with the natural Ruminococcus and Fibrobacter bacteria that are already present in the rumen (Gobius et al 2002). An interesting report of cellulose degradation by Clostridium phytofermentans showed that a single endo-processive GH9 cellulase was a requisite for cellulose degradation (Tolonen et al 2009).…”
Section: The Case Study Of Trans-inoculationmentioning
confidence: 99%